Appendicitis in De Garengeot's Hernia Presenting as a Nontender Inguinal Mass: Case Report and Review of the Literature. (4th March 2014) - Ahmed, K.; Bashar, K.; McHugh, T. J.; McHugh, S. M.; Kavanagh, E.
Abstract : Introduction . De Garengeot first described a femoral hernia containing the appendix in 1731. Appendicitis occurring in this rare clinical setting represents a challenge in diagnosis and management. Case Presentation . We present the case of a 71-year-old male with a three-day history of a nontender inguinal mass. Computed tomography (CT) suggested a femoral hernia. Intraoperatively, the hernia sac was noted to contain a perforated appendix. Discussion . This is an infrequently reported clinical scenario and only the 14th reported case in peer-reviewed literature which includes preoperative CT images. Our case adds to previously reported low sensitivity of CT for diagnosing De Garengeot's hernia. Furthermore, unlike our case the vast majority of previous reports noted a painful inguinal swelling. Conclusion . Perforated appendicitis in a femoral hernia is an extremely uncommon presentation. However, consideration should be given to De Garengeot's hernia in patients with a groin mass, even if nontender.